THE EFFECT OF PRODUCT QUALITY AND PRODUCT REPUTATION ON PURCHASE INTENTION: CASE ON MSME SOY MILK AT EAST LAMPUNG PROVINCE - Miswan Gumanti; Citrawati Jatiningrum; Sudewi Sudewi; Muhammad Faris Afif (JURNAL ILMIAH EDUNOMIKA, 2024)
Expansion growth and competition in the Micro Small and Medium Enterprises (MSME) business products are very varied and highly innovative, therefore consumers have a variety of choices and alternative products according to what consumers intention. A lot of competitive products in the MSME requires business owners to use all their abilities to be able to dominate and conquer the market. The research aims to examine the effect of product quality and product reputation on consumer purchase intention. The sample for this research is consumers of MSME Soy Milk products in Way Jepara Regency, East Lampung Province. Using multiple regression analysis techniques proves that there is a significant impact for product quality and reputation simultaneously on consumer purchase intention. The research results reveal that individually product quality and reputation have an effect on consumer purchase intention in MSME soy milk products. This research provides evidence that MSME are of great importance to improve product quality for increasing consumer purchase intention, and also intensify innovation, various sales strategies to improve the reputation of the products sold. Keywords: Product Quality, Product Reputation, Purchase Intention, MSME